Potential Use of Oleaginous Rhodotorula glutinis for Bioconversion of Palm Oil Mill Effluent and Crude Glycerol to Oil Feedstock for Biodiesel Production - Chanika Saenge (Prince of Songkla University, 2016)
Thesis (Ph.D., Environmental Management)--Prince of Songkla University, 2010